북한이탈주민의 경제범죄 피해 경험이 행동 및 심리적 대응방식에 미치는 영향 - 최영관; 박성철 (한국해양경찰학회보, 12(2), 2022)
이 논문은 국내 정착 북한이탈주민들이 남한 사람들에 비해 높은 범죄율과 범죄 피해율 그리고 국내정착 중 일부의 재입북 및 제3국가로 이주가 빈번해 짐에 따라 이러한 현상들이 국내 정착 실패와 관련된 것으로 보고, 이에 대한 문제의식으로써 이들의 경제범죄 피해와 그에 따른 삶의 대응방식 변화 등 범죄피해가 미치는 삶의 변화를 살펴봄으로써 북한이탈주민 대상 올바른 정착 지원정책을 제언하고자 하였다. 국내 북한이탈주민 305명을 대상으로 실시한 설문조사를 바탕으로 이들이 ‘사기’ 등경제범죄 피해에 따라 이후 삶의 대응방식(사전주의, 회피 및 보호, 범죄적대응 및 사회적심리감)에 있어서 변화를 파악하기 위해 t-테스트를 실시한 결과, 이들은 경제범죄 피해에 따라 사전주의 중 기존 경제활동 방식에 미미한 변화를 가미하는 정도의 소극적 대응방식을 보이고 있으며 또한, 피해경험이 없는 사람들보다 오히려 가해자 대상 모욕 등 인신공격을 자제하는 등 피해 소문의 확산을 거부하는 것으로 나타났다. 이와 관련, 향후 북한이탈주민의 경제범죄 피해를 최소화 하는 등 효율적인 정착 지원을 위해 남한사회 정착 북한이탈주민 대상 국내 경제 및 피해구제 관련 법령 교육, 최근 범죄피해 동향 전파 등 신변보호 경찰의 임무 확대, 보호협력 네트워크(지 자체, 관할 경찰서, 통일부, 시민단체) 설립 등을 각각 제언하였다. This thesis considers these phenomena to be related to the failure to settle in Korea, as North Korean defectors who have settled in Korea have a higher crime rate and crime victimization rate than South Koreans, and some of them re-enter North Korea and migrate to a third country frequently during their resettlement. By examining the changes in their lives that are affected by crime, such as the victims of crime and the changes in their way of responding to them, as a problem awareness, it is intended to suggest a correct settlement support policy for North Korean defectors. Based on a survey conducted on about 305 North Korean defectors in Korea, to identify changes in their lives (precaution, avoidance and protection, criminal response and social psychology) after they suffered economic crimes such as fraud. As a result of conducting the t-test for harm, they showed a passive response method to the extent of adding insignificant changes to the existing economic activity during precautionary measures according to the damage caused by economic crimes. It was found that they refused to spread the news of the damage, such as restraining themselves. In this regard, in order to provide efficient settlement support policy such as minimizing the economic crime damage of North Korean defectors in the future, education on laws and regulations related to the domestic economy and damage relief for North Korean defectors who have settled in South Korea, expansion of police duties for personal protection such as dissemination of recent crime victimization trends, and the establishment of protection cooperation network(local governments, local police stations, the Ministry of Unification, and civic groups) was suggested, respectively. KCI Citation Count: 0